Beyond a Spectacular Image of the Working Class. Issue 4 (2nd October 2019) - Calder, James; Umland, Charlie
ABSTRACT: The Situationist Internationale (SI) were a group of artists, theorists and revolutionaries active in the late '50s and '60s in continental Europe, particularly in France. While the SI remains relatively well known today, for their involvement with the rebellion of students and workers in Paris in May 1968, much of their work has been misunderstood in recent years. This article aims to correct misunderstandings of the SI by emphasizing materialist elements within their critique of society. Additionally, the article will examine the SI's theoretical and practical work in May' 68 and beyond while applying these ideas to modern times and especially the uprising of the "Yellow Vest" movement throughout France. Through this analysis the article concludes that working class movements are often misunderstood and even sabotaged by the establishment left and argues for the importance of viewing instances of working class rebellion within the context of the working class itself.